Science Literacy: Concepts, Contexts, and Consequences - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Science is a way of knowing about the world. At once a process, a product, and an institution, science enables people to both engage in the construction of new knowledge as well as use information to achieve desired ends. Access to science—whether using knowledge or creating it—necessitates some level of familiarity with the enterprise and practice of science: we refer to this as science literacy.
Keywords: Education

Communities, Climate Change, and Health Equity: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
As the effects of climate change become more widespread and significant, communities least able to respond are bearing the largest burden. In the United States, communities disadvantaged by a legacy of racial segregation and environmental injustice struggle with disparate health outcomes, are vulnerable to the effects of climate change (e.g., severe flooding in low-lying areas and extreme heat in urban neighborhoods), and lack sufficient resources to recover from and rebuild for resilience against future events. On October 12 and 14, 2021, the 2-day virtual workshop "Communities, Climate Change, and Health Equity - A New Vision" brought together environmental health experts, resilience practitioners, climate scientists, and people with lived experience to discuss the disproportionate impact of climate change on communities experiencing health disparities and environmental injustice. During the workshop, the first in a four-part series, 41 speakers shared their perspectives on the topic and suggested specific actions that decision-makers can take to address the intersecting crises of climate change and health inequity. This publication summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies

Advancing Health and Resilience in the Gulf of Mexico Region: A Roadmap for Progress - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Consequences of natural disasters and the COVID-19 pandemic have taken a cumulative toll on the health and well-being of people in the Gulf of Mexico region. Long-standing societal challenges related to racism, poverty, education, housing, and underemployment are compounding the trauma, leading to chronic stress for many Gulf residents. The Committee on Progress Toward Human Health and Community Resilience in the Gulf of Mexico Region new report, Advancing Health and Community Resilience in the Gulf of Mexico Region: A Roadmap for Progress, explores key challenges and priorities in Gulf states, including Alabama, Florida, Louisiana, Mississippi, and Texas and evaluates recent progress. The report also makes recommendations for closing critical gaps and implementing transformative approaches that focus on the diverse needs and experiences of people who live and work in the Gulf region.
Keywords: Health and Medicine; Environment and Environmental Studies

Advancing the Framework for Assessing Causality of Health and Welfare Effects to Inform National Ambient Air Quality Standard Reviews - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
As part of its responsibilities under the Clean Air Act, the U.S. Environmental Protection Agency sets National Ambient Air Quality Standards (NAAQS) for the air pollutants carbon monoxide, lead, oxides of nitrogen, particulate matter, ozone, and sulfur dioxide. EPA uses a "weight of evidence approach" to evaluate evidence from scientific studies and describe the causal relationships between these "criteria pollutants" and any adverse impacts on human health and on public welfare - including impacts on wildlife, water, forests, agriculture, and climate. The evaluation, called an Integrated Science Assessment, is used to inform standards setting associated with the criteria pollutants. This report, produced at the request of EPA, describes EPAs and several other frameworks for inferring causality of health or welfare effects and the characteristics of evidence useful for forming a causal determination. The report concludes that EPAs causal framework is effective, reliable, and scientifically defensible, provided that key scientific questions are identified and a range of necessary expertise is engaged. More transparency in how EPA integrates evidence could improve confidence in their determinations, and more guidance is needed in the framework on how evidence should be examined for vulnerable groups (e.g., human sub-populations) and sensitive ecosystems or species.
Keywords: Environment and Environmental Studies

Understanding and Responding to Global Health Security Risks from Microbial Threats in the Arctic: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The National Academies of Sciences, Engineering, and Medicine in collaboration with the InterAcademy Partnership and the European Academies Science Advisory Committee held a workshop in November 2019 to bring together researchers and public health officials from different countries and across several relevant disciplines to explore what is known, and what critical knowledge gaps remain, regarding existing and possible future risks of harmful infectious agents emerging from thawing permafrost and melting ice in the Arctic region. The workshop examined case studies such as the specific case of Arctic region anthrax outbreaks, as a known, observed risk as well as other types of human and animal microbial health risks that have been discovered in snow, ice, or permafrost environments, or that could conceivably exist. The workshop primarily addressed two sources of emerging infectious diseases in the arctic: (1) new diseases likely to emerge in the Arctic as a result of climate change (such as vector-borne diseases) and (2) ancient and endemic diseases likely to emerge in the Arctic specifically as a result of permafrost thaw. Participants also considered key research that could advance knowledge including critical tools for improving observations, and surveillance to advance understanding of these risks, and to facilitate and implement effective early warning systems. Lessons learned from efforts to address emerging or re-emerging microbial threats elsewhere in the world were also discussed. This publication summarizes the presentation and discussion of the workshop.
Keywords: Earth Sciences; Health and Medicine

Climate Change, the Indoor Environment, and Health - Institute of Medicine (The National Academies Press, 2011)
The indoor environment affects occupants' health and comfort. Poor environmental conditions and indoor contaminants are estimated to cost the U.S. economy tens of billions of dollars a year in exacerbation of illnesses like asthma, allergic symptoms, and subsequent lost productivity. Climate change has the potential to affect the indoor environment because conditions inside buildings are influenced by conditions outside them. Climate Change, the Indoor Environment, and Health addresses the impacts that climate change may have on the indoor environment and the resulting health effects. It finds that steps taken to mitigate climate change may cause or exacerbate harmful indoor environmental conditions. The book discusses the role the Environmental Protection Agency (EPA) should take in informing the public, health professionals, and those in the building industry about potential risks and what can be done to address them. The study also recommends that building codes account for climate change projections; that federal agencies join to develop or refine protocols and testing standards for evaluating emissions from materials, furnishings, and appliances used in buildings; and that building weatherization efforts include consideration of health effects. Climate Change, the Indoor Environment, and Health is written primarily for the EPA and other federal agencies, organizations, and researchers with interests in public health; the environment; building design, construction, and operation; and climate issues.
Keywords: Health and Medicine; Environment and Environmental Studies; Engineering and Technology

Forest Health and Biotechnology: Possibilities and Considerations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The American chestnut, whitebark pine, and several species of ash in the eastern United States are just a few of the North American tree species that have been functionally lost or are in jeopardy of being lost due to outbreaks of pathogens and insect pests. New pressures in this century are putting even more trees at risk. Expanded human mobility and global trade are providing pathways for the introduction of nonnative pests for which native tree species may lack resistance. At the same time, climate change is extending the geographic range of both native and nonnative pest species. Biotechnology has the potential to help mitigate threats to North American forests from insects and pathogens through the introduction of pest-resistant traits to forest trees. However, challenges remain: the genetic mechanisms that underlie trees' resistance to pests are poorly understood; the complexity of tree genomes makes incorporating genetic changes a slow and difficult task; and there is a lack of information on the effects of releasing new genotypes into the environment. Forest Health and Biotechnology examines the potential use of biotechnology for mitigating threats to forest tree health and identifies the ecological, economic, and social implications of deploying biotechnology in forests. This report also develops a research agenda to address knowledge gaps about the application of the technology.
Keywords: Environment and Environmental Studies; Biology and Life Sciences

Protecting the Health and Well-Being of Communities in a Changing Climate: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
On March 13, 2017, the Roundtable on Environmental Health Sciences, Research, and Medicine and the Roundtable on Population Health Improvement jointly convened a 1-day public workshop in Washington, DC, to explore potential strategies for public health, environmental health, health care, and related stakeholders to help communities and regions to address and mitigate the health effects of climate change. Participants discussed the perspectives of civic, government, business, and health-sector leaders, and existing research, best practices, and examples that inform stakeholders and practitioners on approaches to support mitigation of and adaptation to climate change and its effects on population health. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Environment and Environmental Studies

The Nexus of Biofuels, Climate Change, and Human Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Liquid fuels are a major part of modern life. They supply energy for ground, water, and air transportation as well as power for industrial and farming machinery. But fossil fuels - the dominant liquid fuel in use for well over a century - have many disadvantages. The use of fossil fuels has obvious health downsides, such as emissions of pollutants that are directly harmful to health. The burning of fossil fuels produces greenhouse gases, which contribute to global warming, itself a long-term threat to human health. There have also been health concerns related to insecurity of liquid fuel supplies and the potential of international conflicts being caused by fuel scarcity. Furthermore, there are concerns that the world's large but still limited supply of fossil fuels could be strained by the increasing demand that results from societies around the world achieving greater prosperity. In the face of these concerns, new policies have been created that encourage the development of renewable sources of energy in general and biofuels in particular. In January 2013, the Roundtable on Environmental Health Sciences, Research, and Medicine of the Institute of Medicine held a 2- day, interactive, public workshop on the intersection of biofuels, climate change, and human health. Workshop attendees explored public health issues related to the composition of traditional and alternative fuels and fuel additives, and they discussed the known and potential health impacts associated with the use of these fuels and fuel additives. The Nexus of Biofuels, Climate Change, and Human Health is the summary of that workshop. This report examines air, water, land use, food, and social impacts of biomass feedstock as an energy resource, and the state of the science and health policy implications of using different types (and generations) of biofuels as an energy source.
Keywords: Health and Medicine

Modeling the Health Risks of Climate Change: Workshop Summary - National Research Council (The National Academies Press, 2015)
Climate change poses risks to human health and well-being through shifting weather patterns, increases in frequency and intensity of heat waves and other extreme weather events, rising sea levels, ocean acidification, and other environmental effects. Those risks occur against a backdrop of changing socioeconomic conditions, medical technology, population demographics, environmental conditions, and other factors that are important in determining health. Models of health risks that reflect how health determinants and climate changes vary in time and space are needed so that we can inform adaptation efforts and reduce or prevent adverse health effects. Robust health risk models could also help to inform national and international discussions about climate policies and the economic consequences of action and inaction. Interest in resolving some of the challenges facing health effects modelers and health scientists led the National Research Council's Standing Committee on Emerging Science for Environmental Health Decisions to hold a workshop on November 3-4, 2014, in Washington, DC, to explore new approaches to modeling the human health risks of climate change. Throughout the workshop, the discussions highlighted examples of current application of models, research gaps, lessons learned, and potential next steps to improve modeling of health risks associated with climate change. Modeling the Health Risks of Climate Change summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies

Including Health in Global Frameworks for Development, Wealth, and Climate Change: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Including Health in Global Frameworks for Development, Wealth, and Climate Change is the summary of a three-part public webinar convened by the Institute of Medicine Roundtable on Environmental Health Sciences, Research, and Medicine and its collaborative on Global Environmental Health and Sustainable Development. Presenters and participants discussed the role of health in measuring a country's wealth (going beyond gross domestic product), health scenario communication, and international health goals and indicators. The workshop focused on fostering discussion across academic, government, business, and civil society sectors to make use of existing data and information that can be adapted to track progress of global sustainable development and human health. This report examines frameworks for global development goals and connections to health indicators, the role for health in the context of novel sustainable economic frameworks that go beyond gross domestic product, and scenarios to project climate change impacts.
Keywords: Health and Medicine

Review of the Draft Interagency Report on the Impacts of Climate Change on Human Health in the United States - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The U.S. National Climate Assessment identified a number of ways in which climate change is affecting, and is likely to affect, people, infrastructure, natural resources, and ecosystems. Those impacts, in turn, are increasingly having important current and potential future consequences for human health. There is a need to probe more deeply into how climate change impacts on the environment can create environmental stressors that, in turn, are having and/or have the potential to have significant impact on human health in a number of dimensions. In response to this need, the U.S. Global Change Research Program (USGCRP) has initiated an interagency Scientific Assessment on the Impacts of Climate Change on Human Health in the United States. The Assessment is intended to inform public health authorities, other planning and policy entities, and the general public. Review of the Draft Interagency Report on the Impacts of Climate Change on Human Health in the United States evaluates the scientific basis, findings, and key messages of the USGCRP Draft Assessment. This report offers a number of overarching suggestions on how the USGCRP report authors can enhance their identification and assessment of the science and better communicate their conclusions to all of their target audiences. These recommendations this help the Assessment to play a significant role in continued efforts to examine and explore the impacts of climate change on human health.
Keywords: Environment and Environmental Studies; Health and Medicine

Toward Understanding the Interplay of Environmental Stressors, Infectious Diseases, and Human Health: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Infectious diseases are among the top five leading causes of death worldwide. Scientists have long known that the environment plays a defining role in the emergence and spread of infectious diseases. However, the relationships among human exposures to environmental pollution; rapid environmental change; and the emergence, spread, and persistence of infectious diseases are not yet well understood. Emerging findings suggest that exposure to environmental pollutants such as airborne particulate matter, industrial chemicals, and heavy metals may alter the immune system, increasing human susceptibility to infection. New research findings show that the microbiome of humans and ecosystems also play important roles in infection. Nonetheless, the fields of environmental health and infectious diseases largely operate distinctly from one another even though research on the interplay between these fields could inform new health practices, public health research, and public health policy.
Keywords: Health and Medicine

Understanding the Connections Between Coastal Waters and Ocean Ecosystem Services and Human Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Understanding the Connections Between Coastal Waters and Ocean Ecosystem Services and Human Health discusses the connection of ecosystem services and human health. This report looks at the state of the science of the role of oceans in ensuring human health and identifies gaps and opportunities for future research. The report summarizes a workshop convened by the Institute of Medicine's Roundtable on Environmental Health Sciences, Research, and Medicine. Participants discussed coastal waters and ocean ecosystem services in the United States in an effort to understand impacts on human health. Understanding the Connections Between Coastal Waters and Ocean Ecosystem Services and Human Health focuses on key linkages by discussing the ecosystem services provided by coastal waterways and oceans that are essential for human health and well-being; examining the major stressors that affect the ability of coastal waterways and ocean systems to provide essential services; and considering key factors that can enhance the resiliency of these systems.
Keywords: Health and Medicine

Perspectives on Climate and Environmental Justice on the U.S. Gulf Coast: Proceedings of a Webinar–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Communities along the Gulf Coast routinely experience intense weather events. Acute and repetitive shocks - illustrated by the multiple Gulf regional hurricane landfalls during the 2020 hurricane season - have a disproportionate impact on communities in this region that are already burdened by chronic stressors such as systemic and structural racism, poverty, environmental degradation, and health disparities. Climate change threatens to exacerbate the severity of these impacts as disadvantaged and underserved communities fall further behind in their ability to prepare for, respond to, mitigate, or recover from disasters. On June 24, 2021, the Gulf Research Program of the National Academies of Sciences, Engineering, and Medicine convened a panel of three members of the White House Environmental Justice Advisory Council to discuss steps that are being taken or that need to occur to advance climate and environmental justice for those who call the Gulf of Mexico region home. The panelists discussed opportunities to equitably improve conditions in the Gulf of Mexico region, particularly within Black, Indigenous, and People of Color communities. This event provided important perspective, though much work remains to elevate and examine the climate and environmental justice priorities of diverse communities, particularly Indigenous people, and to identify the mechanisms necessary to implement the recommendations offered by the panel members. This publication summarizes the discussion.
Keywords: Environment and Environmental Studies

Wildland Fires: Toward Improved Understanding and Forecasting of Air Quality Impacts: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Wildland fires pose a growing threat to air quality and human health. Fire is a natural part of many landscapes, but the extent of area burned and the severity of fires have been increasing, concurrent with human movement into previously uninhabited fire-prone areas and forest management practices that have increased fuel loads. These changes heighten the risk of exposure to fire itself and emissions (smoke), which can travel thousands of miles and affect millions of people, creating local, regional, and national air quality and health concerns. To address this growing threat, the National Academies brought together atmospheric chemistry and health research communities, natural resource managers, and decision makers to discuss current knowledge and needs surrounding how wildland fire emissions affect air quality and human health. Participants also explored opportunities to better bridge these communities to advance science and improve the production and exchange of information. This publication summarizes the workshop discussions and themes that emerged throughout the meeting.
Keywords: Earth Sciences

Healthy, Resilient, and Sustainable Communities After Disasters: Strategies, Opportunities, and Planning for Recovery - Institute of Medicine (The National Academies Press, 2015)
In the devastation that follows a major disaster, there is a need for multiple sectors to unite and devote new resources to support the rebuilding of infrastructure, the provision of health and social services, the restoration of care delivery systems, and other critical recovery needs. In some cases, billions of dollars from public, private and charitable sources are invested to help communities recover. National rhetoric often characterizes these efforts as a "return to normal." But for many American communities, pre-disaster conditions are far from optimal. Large segments of the U.S. population suffer from preventable health problems, experience inequitable access to services, and rely on overburdened health systems. A return to pre-event conditions in such cases may be short-sighted given the high costs - both economic and social - of poor health. Instead, it is important to understand that the disaster recovery process offers a series of unique and valuable opportunities to improve on the status quo. Capitalizing on these opportunities can advance the long-term health, resilience, and sustainability of communities - thereby better preparing them for future challenges. Healthy, Resilient, and Sustainable Communities After Disasters identifies and recommends recovery practices and novel programs most likely to impact overall community public health and contribute to resiliency for future incidents. This book makes the case that disaster recovery should be guided by a healthy community vision, where health considerations are integrated into all aspects of recovery planning before and after a disaster, and funding streams are leveraged in a coordinated manner and applied to health improvement priorities in order to meet human recovery needs and create healthy built and natural environments. The conceptual framework presented in Healthy, Resilient, and Sustainable Communities After Disasters lays the groundwork to achieve this goal and provides operational guidance for multiple sectors involved in community planning and disaster recovery. Healthy, Resilient, and Sustainable Communities After Disasters calls for actions at multiple levels to facilitate recovery strategies that optimize community health. With a shared healthy community vision, strategic planning that prioritizes health, and coordinated implementation, disaster recovery can result in a communities that are healthier, more livable places for current and future generations to grow and thrive - communities that are better prepared for future adversities.
Keywords: Health and Medicine; Conflict and Security Issues

Accelerating Decarbonization in the United States: Technology, Policy, and Societal Dimensions - Transportation Research Board; National Academy of Engineering; National Academy of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Addressing climate change is essential and possible, and it offers a host of benefits - from better public health to new economic opportunities. The United States has a historic opportunity to lead the way in decarbonization by transforming its current energy system to one with net-zero emissions of carbon dioxide. Recent legislation has set the nation on the path to reach its goal of net zero by 2050 in order to avoid the worst consequences of climate change. However, even if implemented as designed, current policy will get the United States only part of the way to its net-zero goal. Accelerating Decarbonization in the United States provides a comprehensive set of actionable recommendations to help policymakers achieve a just and equitable energy transition over the next decade and beyond, including policy, technology, and societal dimensions. This report addresses federal and subnational policy needs to overcome implementation barriers and gaps with a focus on energy justice, workforce development, public health, and public engagement. The report also presents a suite of recommendations for the electricity, transportation, built environment, industrial, fossil fuels, land use, and finance sectors.
Keywords: Environment and Environmental Studies; Earth Sciences

Cross-Cutting Themes for U.S. Contributions to the UN Ocean Decade - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The ocean is central to the health of the planet and the well-being of human societies, but ongoing depletion, disruption, and pollution threaten its future. The United Nations proclaimed 2021-2030 the Decade of Ocean Science for Sustainable Development (UN Ocean Decade) in recognition of the need to sustainably manage the Ocean. U.S. participation in the Decade, guided by the U.S. National Committee, included a call for "Ocean-Shots" - ambitious, transformational research concepts that draw from multiple disciplines. More than 100 Ocean-Shots were submitted. Conducted at the request of the White House Office of Science and Technology Policy and sponsored by NASA, this report identifies exciting themes from the Ocean-Shots that will galvanize action and inspire transformative, cross-disciplinary, and multi-generational participation in the Decade. Two foundational themes undergird how to go about science: An Inclusive and Equitable Ocean calls for the involvement of a diverse and representative ocean community, and An Ocean of Data recognizes the shift toward open access for data that is collected. Four topical themes - The Ocean Revealed, The Restored and Sustainable Ocean, Ocean Solutions for Climate Resilience, and Healthy Urban Sea - represent promising areas for research investments that are consistent both with the UN Ocean Decade Outcomes and U.S. ocean priorities.
Keywords: Earth Sciences

Partnerships and Cross-Sector Collaboration Priorities to Support Climate Research and Policy: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
As global mean temperatures rise and extreme climate and weather events increase in frequency and intensity, the severity of the climate situation and its potential impacts on human well-being - particularly of the world's most vulnerable populations - is strikingly evident. Research and policy responses to address climate change are required to meet U.S. targets set for the coming decades, which include a reduction of 50 to 52 percent of greenhouse gas emissions by 2030 and net-zero emissions by 2050. In coordination with other activities on climate, energy, and environmental and human health across the National Academies of Sciences, Engineering, and Medicine, the Government-University-Industry Research Roundtable convened a series of five workshops in June and July of 2021 to discuss opportunities for enhancing U.S. scientific and technological approaches to climate research and policy through cross-sector collaboration and partnerships, and to examine the impacts of climate policy on economic development, inequality, and international competitiveness. This document summarizes the presentations and discussions at the five workshops.
Keywords: Policy for Science and Technology; Environment and Environmental Studies

Behavioral Economics: Policy Impact and Future Directions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Behavioral economics - a field based in collaborations among economists and psychologists - focuses on integrating a nuanced understanding of behavior into models of decision-making. Since the mid-20th century, this growing field has produced research in numerous domains and has influenced policymaking, research, and marketing. However, little has been done to assess these contributions and review evidence of their use in the policy arena. Behavioral Economics: Policy Impact and Future Directions examines the evidence for behavioral economics and its application in six public policy domains: health, retirement benefits, climate change, social safety net benefits, climate change, education, and criminal justice. The report concludes that the principles of behavioral economics are indispensable for the design of policy and recommends integrating behavioral specialists into policy development within government units. In addition, the report calls for strengthening research methodology and identifies research priorities for building on the accomplishments of the field to date.
Keywords: Industry and Labor; Behavioral and Social Sciences

Innovations in the Food System: Exploring the Future of Food: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On August 7–8, 2019, the National Academies of Sciences, Engineering, and Medicine hosted a public workshop in Washington, DC, to review the status of current and emerging knowledge about innovations for modern food systems and strategies for meeting future needs. The workshop addressed different perspectives on the topic of food systems and would build on a workshop on the topic of sustainable diets hosted by the Food Forum in August 2018. This publication summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Biodiversity at Risk: Today's Choices Matter - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
A growing body of evidence has sounded the alarm that the biodiversity that supports and sustains life on Earth is at risk. Habitat destruction, resource exploitation, and climate change are among the many stressors that have put 1 million species under threat of extinction and sharply reduced the populations of many plant and animal species. While researchers and global leaders ramp up efforts to address this existential threat, the significance of species loss and the value of preserving biodiversity is not widely recognized by policy makers or the public. This booklet, produced by an international committee of experts, provides a publicly accessible overview of the many dimensions of biodiversity and why it's vital to the health of all life on the planet. The booklet also examines the causes of biodiversity loss and presents actions that can be taken from the individual to the global level to stop this decline.
Keywords: Biology and Life Sciences

The Influence of Global Environmental Change on Infectious Disease Dynamics: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
The twentieth century witnessed an era of unprecedented, large-scale, anthropogenic changes to the natural environment. Understanding how environmental factors directly and indirectly affect the emergence and spread of infectious disease has assumed global importance for life on this planet. While the causal links between environmental change and disease emergence are complex, progress in understanding these links, as well as how their impacts may vary across space and time, will require transdisciplinary, transnational, collaborative research. This research may draw upon the expertise, tools, and approaches from a variety of disciplines. Such research may inform improvements in global readiness and capacity for surveillance, detection, and response to emerging microbial threats to plant, animal, and human health. The Influence of Global Environmental Change on Infectious Disease Dynamics is the summary of a workshop hosted by the Institute of Medicine Forum on Microbial Threats in September 2013 to explore the scientific and policy implications of the impacts of global environmental change on infectious disease emergence, establishment, and spread. This report examines the observed and potential influence of environmental factors, acting both individually and in synergy, on infectious disease dynamics. The report considers a range of approaches to improve global readiness and capacity for surveillance, detection, and response to emerging microbial threats to plant, animal, and human health in the face of ongoing global environmental change.
Keywords: Health and Medicine; Conflict and Security Issues

A Framework for Assessing Effects of the Food System - Institute of Medicine; National Research Council (The National Academies Press, 2015)
How we produce and consume food has a bigger impact on Americans' well-being than any other human activity. The food industry is the largest sector of our economy; food touches everything from our health to the environment, climate change, economic inequality, and the federal budget. From the earliest developments of agriculture, a major goal has been to attain sufficient foods that provide the energy and the nutrients needed for a healthy, active life. Over time, food production, processing, marketing, and consumption have evolved and become highly complex. The challenges of improving the food system in the 21st century will require systemic approaches that take full account of social, economic, ecological, and evolutionary factors. Policy or business interventions involving a segment of the food system often have consequences beyond the original issue the intervention was meant to address. A Framework for Assessing Effects of the Food System develops an analytical framework for assessing effects associated with the ways in which food is grown, processed, distributed, marketed, retailed, and consumed in the United States. The framework will allow users to recognize effects across the full food system, consider all domains and dimensions of effects, account for systems dynamics and complexities, and choose appropriate methods for analysis. This report provides example applications of the framework based on complex questions that are currently under debate: consumption of a healthy and safe diet, food security, animal welfare, and preserving the environment and its resources. A Framework for Assessing Effects of the Food System describes the U.S. food system and provides a brief history of its evolution into the current system. This report identifies some of the real and potential implications of the current system in terms of its health, environmental, and socioeconomic effects along with a sense for the complexities of the system, potential metrics, and some of the data needs that are required to assess the effects. The overview of the food system and the framework described in this report will be an essential resource for decision makers, researchers, and others to examine the possible impacts of alternative policies or agricultural or food processing practices.
Keywords: Food and Nutrition; Agriculture

Review of the Draft Fifth National Climate Assessment - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Roughly every four years, the U.S. Global Change Research Program produces a congressionally mandated assessment of global change science and the impacts, adaptation, and mitigation of climate change in the United States. The draft Fifth National Climate Assessment (NCA5), released publicly in November 2022, covers a wide range of U.S. impacts, from human health and community well-being to the built environment, businesses and economies, and ecosystems and water resources. NCA5 had the largest scale of collaboration to date in the series, with input from hundreds of experts from all levels of governments, academia, non-government organizations, the private sector, and the public. The National Academies report provides an independent, comprehensive review and makes recommendations to strengthen the accuracy, credibility, and accessibility of the draft NCA5 report. The National Academies’ review of the draft NCA5 report finds that it successfully meets the requirements of the federal mandate, provides accurate information, and effectively communicates climate science to the public, decision makers, and other stakeholders. The review makes recommendations for ways the draft NCA5 report could be strengthened, including: adopting more clear and consistent structure for key messages and figures across the report; resolving inconsistencies between chapters in how terms and topics are discussed, for example the use of scenarios and projections; intentionally applying an equity and justice lens across chapters; and increasing emphasis on certain topical areas.
Keywords: Environment and Environmental Studies; Behavioral and Social Sciences

Future Directions for Southern Ocean and Antarctic Nearshore and Coastal Research - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Antarctica hosts some of the harshest and most remote environments on Earth - and it is a region of vital importance for scientific research. The environment and position of Antarctica on the globe mean that research conducted there can offer unique insights on important Earth processes, including rising sea level, the carbon cycle, ecosystem structure. As the climate warms, data gathered from Antarctic research will be essential to understanding how Earth processes are changing and the potential social, economic, and health impacts on both U.S. and global populations. This report identifies the highest priorities for research in the Southern Ocean and nearshore and coastal Antarctica, as well as gaps in current capabilities to support this research. Global sea level rise, heat and carbon budgets, and changing ecosystems are the three highest-priority science drivers for research in the region. To address those drivers and maintain a robust U.S. research presence in this vitally important region, investments are needed in the U.S. Antarctic program and its research platforms, including the development of new technologies and the replacement of aging icebreaking research vessels. Additionally, the U.S. should strengthen relationships with other nations’ Antarctic programs that can help support these essential science drivers.
Keywords: Earth Sciences

Climate Change Education in Formal Settings, K-14: A Workshop Summary - National Research Council (The National Academies Press, 2012)
Climate change is occurring, is very likely caused by human activities, and poses significant risks for a broad range of human and natural systems. Each additional ton of greenhouse gases emitted commits us to further change and greater risks. In the judgment of the Committee on America's Climate Choices, the environmental, economic, and humanitarian risks of climate change indicate a pressing need for substantial action to limit the magnitude of climate change and to prepare to adapt to its impacts. A principal message from the recent National Research Council report, America's Climate Choices, this brief summary of how climate change will shape many aspects of life in the foreseeable future emphasizes the vital importance of preparation for these changes.
Keywords: Earth Sciences; Education

Accelerating Decarbonization of the U.S. Energy System - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The world is transforming its energy system from one dominated by fossil fuel combustion to one with net-zero emissions of carbon dioxide (CO2), the primary anthropogenic greenhouse gas. This energy transition is critical to mitigating climate change, protecting human health, and revitalizing the U.S. economy. To help policymakers, businesses, communities, and the public better understand what a net-zero transition would mean for the United States, the National Academies of Sciences, Engineering and Medicine convened a committee of experts to investigate how the U.S. could best decarbonize its transportation, electricity, buildings, and industrial sectors. This report, Accelerating Decarbonization of the United States Energy System, identifies key technological and socio-economic goals that must be achieved to put the United States on the path to reach net-zero carbon emissions by 2050. The report presents a policy blueprint outlining critical near-term actions for the first decade (2021-2030) of this 30-year effort, including ways to support communities that will be most impacted by the transition.
Keywords: Environment and Environmental Studies; Energy and Energy Conservation

A Review of the U.S. Global Change Research Program's Draft Strategic Plan - National Research Council (The National Academies Press, 2012)
The U.S. government supports a large, diverse suite of activities that can be broadly characterized as "global change research." Such research offers a wide array of benefits to the nation, in terms of protecting public health and safety, enhancing economic strength and competitiveness, and protecting the natural systems upon which life depends. The U.S. Global Change Research Program (USGCRP), which coordinates the efforts of numerous agencies and departments across the federal government, was officially established in 1990 through the U.S. Global Change Research Act (GCRA). In the subsequent years, the scope, structure, and priorities of the Program have evolved, (for example, it was referred to as the Climate Change Science Program [CCSP] for the years 2002-2008), but throughout, the Program has played an important role in shaping and coordinating our nation's global change research enterprise. This research enterprise, in turn, has played a crucial role in advancing understanding of our changing global environment and the countless ways in which human society affects and is affected by such changes.
Keywords: Environment and Environmental Studies; Earth Sciences

Global Climate Change and Extreme Weather Events: Understanding the Contributions to Infectious Disease Emergence: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
Long before the "germ theory" of disease was described, late in the nineteenth century, humans knew that climatic conditions influence the appearance and spread of epidemic diseases. Ancient notions about the effects of weather and climate on disease remain embedded in our collective consciousness-through expressions such as "cold" for rhinovirus infections; "malaria," derived from the Latin for "bad air;" and the common complaint of feeling "under the weather." Today, evidence is mounting that earth's climate is changing at a faster rate than previously appreciated, leading researchers to view the longstanding relationships between climate and disease with new urgency and from a global perspective. On December 4 and 5, 2007, the Forum on Microbial Threats hosted a public workshop in Washington, DC to consider the possible infectious disease impacts of global climate change and extreme weather events on human, animal, and plant health, as well as their expected implications for global and national security.
Keywords: Environment and Environmental Studies; Earth Sciences; Health and Medicine

Informing an Effective Response to Climate Change - National Research Council (The National Academies Press, 2010)
Global climate change is one of America's most significant long-term policy challenges. Human activity—especially the use of fossil fuels, industrial processes, livestock production, waste disposal, and land use change—is affecting global average temperatures, snow and ice cover, sea-level, ocean acidity, growing seasons and precipitation patterns, ecosystems, and human health. Climate-related decisions are being carried out by almost every agency of the federal government, as well as many state and local government leaders and agencies, businesses and individual citizens. Decision makers must contend with the availability and quality of information, the efficacy of proposed solutions, the unanticipated consequences resulting from decisions, the challenge of implementing chosen actions, and must consider how to sustain the action over time and respond to new information.
Keywords: Environment and Environmental Studies; Earth Sciences

The Future of Atmospheric Chemistry Research: Remembering Yesterday, Understanding Today, Anticipating Tomorrow - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Our world is changing at an accelerating rate. The global human population has grown from 6.1 billion to 7.1 billion in the last 15 years and is projected to reach 11.2 billion by the end of the century. The distribution of humans across the globe has also shifted, with more than 50 percent of the global population now living in urban areas, compared to 29 percent in 1950. Along with these trends, increasing energy demands, expanding industrial activities, and intensification of agricultural activities worldwide have in turn led to changes in emissions that have altered the composition of the atmosphere.
Keywords: Earth Sciences

Reckoning with the U.S. Role in Global Ocean Plastic Waste - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
An estimated 8 million metric tons (MMT) of plastic waste enters the world's ocean each year - the equivalent of dumping a garbage truck of plastic waste into the ocean every minute. Plastic waste is now found in almost every marine habitat, from the ocean surface to deep sea sediments to the ocean's vast mid-water region, as well as the Great Lakes. This report responds to a request in the bipartisan Save Our Seas 2.0 Act for a scientific synthesis of the role of the United States both in contributing to and responding to global ocean plastic waste. The United States is a major producer of plastics and in 2016, generated more plastic waste by weight and per capita than any other nation. Although the U.S. solid waste management system is advanced, it is not sufficient to deter leakage into the environment. Reckoning with the U.S. Role in Global Ocean Plastic Waste calls for a national strategy by the end of 2022 to reduce the nation's contribution to global ocean plastic waste at every step - from production to its entry into the environment - including by substantially reducing U.S. solid waste generation. This report also recommends a nationally-coordinated and expanded monitoring system to track plastic pollution in order to understand the scales and sources of U.S. plastic waste, set reduction and management priorities, and measure progress.
Keywords: Environment and Environmental Studies

Science Breakthroughs to Advance Food and Agricultural Research by 2030 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
For nearly a century, scientific advances have fueled progress in U.S. agriculture to enable American producers to deliver safe and abundant food domestically and provide a trade surplus in bulk and high-value agricultural commodities and foods. Today, the U.S. food and agricultural enterprise faces formidable challenges that will test its long-term sustainability, competitiveness, and resilience. On its current path, future productivity in the U.S. agricultural system is likely to come with trade-offs. The success of agriculture is tied to natural systems, and these systems are showing signs of stress, even more so with the change in climate.
Keywords: Agriculture; Food and Nutrition; Earth Sciences; Environment and Environmental Studies

Environmental Engineering for the 21st Century: Addressing Grand Challenges - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Environmental engineers support the well-being of people and the planet in areas where the two intersect. Over the decades the field has improved countless lives through innovative systems for delivering water, treating waste, and preventing and remediating pollution in air, water, and soil. These achievements are a testament to the multidisciplinary, pragmatic, systems-oriented approach that characterizes environmental engineering. Environmental Engineering for the 21st Century: Addressing Grand Challenges outlines the crucial role for environmental engineers in this period of dramatic growth and change. The report identifies five pressing challenges of the 21st century that environmental engineers are uniquely poised to help advance: sustainably supply food, water, and energy; curb climate change and adapt to its impacts; design a future without pollution and waste; create efficient, healthy, resilient cities; and foster informed decisions and actions.
Keywords: Engineering and Technology; Earth Sciences

Review of the Draft Fourth National Climate Assessment - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Climate change poses many challenges that affect society and the natural world. With these challenges, however, come opportunities to respond. By taking steps to adapt to and mitigate climate change, the risks to society and the impacts of continued climate change can be lessened. The National Climate Assessment, coordinated by the U.S. Global Change Research Program, is a mandated report intended to inform response decisions. Required to be developed every four years, these reports provide the most comprehensive and up-to-date evaluation of climate change impacts available for the United States, making them a unique and important climate change document.
Keywords: Earth Sciences; Environment and Environmental Studies

Review of the Bureau of Ocean Energy Management "Air Quality Modeling in the Gulf of Mexico Region" Study - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Emissions associated with oil and gas exploration, development, and production on the Gulf waters can result in increased levels of air pollutants that contribute to a range of air quality impacts in the Gulf of Mexico Region (GOMR). "Criteria air pollutants", such as carbon monoxide, lead, nitrogen dioxide, ozone, particulate matter, and sulfur dioxide, are considered harmful to public health and the environment. The Bureau of Ocean Energy Management (BOEM) manages the U.S. outer continental shelf oil and gas resources and is required to help manage air quality in the GOMR.
Keywords: Environment and Environmental Studies; Earth Sciences

Assessment of Approaches to Updating the Social Cost of Carbon: Phase 1 Report on a Near-Term Update - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The social cost of carbon (SCC) for a given year is an estimate, in dollars, of the present discounted value of the damage caused by a 1-metric ton increase in CO2 emissions into the atmosphere in that year; or equivalently, the benefits of reducing CO2 emissions by the same amount in that given year. The SCC is intended to provide a comprehensive measure of the monetized value of the net damages from global climate change from an additional unit of CO2, including, but not limited to, changes in net agricultural productivity, energy use, human health effects, and property damages from increased flood risk. Federal agencies use the SCC to value the CO2 emissions impacts of various policies including emission and fuel economy standards for vehicles, regulations of industrial air pollutants from industrial manufacturing, emission standards for power plants and solid waste incineration, and appliance energy efficiency standards.
Keywords: Environment and Environmental Studies

Monitoring Climate Change Impacts: Metrics at the Intersection of the Human and Earth Systems - National Research Council (The National Academies Press, 2010)
The stresses associated with climate change are expected to be felt keenly as human population grows to a projected 9 billion by the middle of this century, increasing the demand for resources and supporting infrastructure. Therefore, information to assess vulnerabilities to climate change is needed to support policies and investments designed to increase resilience in human and Earth systems.
Keywords: Environment and Environmental Studies; Earth Sciences

Improving Characterization of Anthropogenic Methane Emissions in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Understanding, quantifying, and tracking atmospheric methane and emissions is essential for addressing concerns and informing decisions that affect the climate, economy, and human health and safety. Atmospheric methane is a potent greenhouse gas (GHG) that contributes to global warming. While carbon dioxide is by far the dominant cause of the rise in global average temperatures, methane also plays a significant role because it absorbs more energy per unit mass than carbon dioxide does, giving it a disproportionately large effect on global radiative forcing. In addition to contributing to climate change, methane also affects human health as a precursor to ozone pollution in the lower atmosphere.
Keywords: Earth Sciences; Environment and Environmental Studies

The Power of Change: Innovation for Development and Deployment of Increasingly Clean Electric Power Technologies - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Electricity, supplied reliably and affordably, is foundational to the U.S. economy and is utterly indispensable to modern society. However, emissions resulting from many forms of electricity generation create environmental risks that could have significant negative economic, security, and human health consequences. Large-scale installation of cleaner power generation has been generally hampered because greener technologies are more expensive than the technologies that currently produce most of our power. Rather than trade affordability and reliability for low emissions, is there a way to balance all three?
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Advancing the Science of Climate Change - National Research Council (The National Academies Press, 2010)
Climate change is occurring, is caused largely by human activities, and poses significant risks for—and in many cases is already affecting—a broad range of human and natural systems. The compelling case for these conclusions is provided in Advancing the Science of Climate Change, part of a congressionally requested suite of studies known as America's Climate Choices. While noting that there is always more to learn and that the scientific process is never closed, the book shows that hypotheses about climate change are supported by multiple lines of evidence and have stood firm in the face of serious debate and careful evaluation of alternative explanations. As decision makers respond to these risks, the nation's scientific enterprise can contribute through research that improves understanding of the causes and consequences of climate change and also is useful to decision makers at the local, regional, national, and international levels. The book identifies decisions being made in 12 sectors, ranging from agriculture to transportation, to identify decisions being made in response to climate change. Advancing the Science of Climate Change calls for a single federal entity or program to coordinate a national, multidisciplinary research effort aimed at improving both understanding and responses to climate change. Seven cross-cutting research themes are identified to support this scientific enterprise. In addition, leaders of federal climate research should redouble efforts to deploy a comprehensive climate observing system, improve climate models and other analytical tools, invest in human capital, and improve linkages between research and decisions by forming partnerships with action-oriented programs.
Keywords: Environment and Environmental Studies; Earth Sciences

A Framework for K-12 Science Education: Practices, Crosscutting Concepts, and Core Ideas - National Research Council (The National Academies Press, 2012)
Science, engineering, and technology permeate nearly every facet of modern life and hold the key to solving many of humanity's most pressing current and future challenges. The United States' position in the global economy is declining, in part because U.S. workers lack fundamental knowledge in these fields. To address the critical issues of U.S. competitiveness and to better prepare the workforce, A Framework for K-12 Science Education proposes a new approach to K-12 science education that will capture students' interest and provide them with the necessary foundational knowledge in the field.
Keywords: Education

Climate Change Education: Preparing Future and Current Business Leaders: A Workshop Summary - National Research Council (The National Academies Press, 2014)
Climate change poses challenges as well as opportunities for businesses and, broadly speaking for the entire economy. Businesses will be challenged to provide services or products with less harmful influence on the climate; respond to a changing policy, regulatory, and market environment; and provide new services and products to help address the challenges of a changing climate. Many businesses are beginning to see climate change as another context within which they need to consider their core functions of strategy, finance, operations, marketing, and their regulatory environments, a context that poses both risks and opportunities. Climate Change Education: Preparing Current and Future Business Leaders is the summary of a workshop hosted by the National Research Council's Board on Science Education in March 2013 to explore issues associated with teaching climate change-related topics in business schools. The workshop focused on major gaps in understanding of climate and sustainability education in postsecondary professional schools of business. The workshop also connected the topic of climate education for current and future business leaders with a broader discussion on climate change education and how they influence and can benefit each other. This report discusses the role that business schools could play in preparing future corporate leaders for the challenges and opportunities that climate change poses.
Keywords: Environment and Environmental Studies; Education; Earth Sciences

Communicating Science Effectively: A Research Agenda - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Science and technology are embedded in virtually every aspect of modern life. As a result, people face an increasing need to integrate information from science with their personal values and other considerations as they make important life decisions about medical care, the safety of foods, what to do about climate change, and many other issues. Communicating science effectively, however, is a complex task and an acquired skill. Moreover, the approaches to communicating science that will be most effective for specific audiences and circumstances are not obvious. Fortunately, there is an expanding science base from diverse disciplines that can support science communicators in making these determinations. Communicating Science Effectively offers a research agenda for science communicators and researchers seeking to apply this research and fill gaps in knowledge about how to communicate effectively about science, focusing in particular on issues that are contentious in the public sphere. To inform this research agenda, this publication identifies important influences – psychological, economic, political, social, cultural, and media-related – on how science related to such issues is understood, perceived, and used.
Keywords: Policy for Science and Technology

A Research Review of Interventions to Increase the Persistence and Resilience of Coral Reefs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Coral reef declines have been recorded for all major tropical ocean basins since the 1980s, averaging approximately 30-50% reductions in reef cover globally. These losses are a result of numerous problems, including habitat destruction, pollution, overfishing, disease, and climate change. Greenhouse gas emissions and the associated increases in ocean temperature and carbon dioxide (CO2) concentrations have been implicated in increased reports of coral bleaching, disease outbreaks, and ocean acidification (OA). For the hundreds of millions of people who depend on reefs for food or livelihoods, the thousands of communities that depend on reefs for wave protection, the people whose cultural practices are tied to reef resources, and the many economies that depend on reefs for fisheries or tourism, the health and maintenance of this major global ecosystem is crucial.
Keywords: Earth Sciences

Review of the U.S. Global Change Research Program's Draft Decadal Strategic Plan, 2022-2031 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
More intense heat waves, extended wildfire seasons and other escalating impacts of climate change have made it more important than ever to fill knowledge gaps that improve society's understanding, assessment, and response to global change. The US Global Change Research Program (USGCRP) - a collection of 13 Federal entities charged by law to help the United States and the world fill those knowledge gaps - laid out proposed mechanisms and priorities for global change research over the next decade in its draft Decadal Strategic Plan 2022-2031. The draft plan recognizes that priority knowledge gaps have shifted over the past decade as demand has grown for more useful and more inclusive data to inform decision-making, and as the focus on resilience and sustainability has increased. As part of its work in advising the USGCRP since 2011, the National Academies reviewed USGCRP's draft plan to determine how it might be enhanced. Advances in the draft plan include an increased emphasis on social sciences, community engagement with marginalized groups, and promotion of diversity, equity, inclusion, and justice in the production of science. Strengthening the interconnections between the plan's core pillars and expanding opportunities for coordination among federal agencies tasked with responding to global climate change would improve the plan. The draft plan could more strongly convey a sense of urgency throughout the plan and would benefit from additional examples of key research outputs that could advance policy and decision making on global change challenges.
Keywords: Earth Sciences; Behavioral and Social Sciences

Disaster Resilience: A National Imperative (The National Academies Press, 2012)
No person or place is immune from disasters or disaster-related losses. Infectious disease outbreaks, acts of terrorism, social unrest, or financial disasters in addition to natural hazards can all lead to large-scale consequences for the nation and its communities. Communities and the nation thus face difficult fiscal, social, cultural, and environmental choices about the best ways to ensure basic security and quality of life against hazards, deliberate attacks, and disasters. Beyond the unquantifiable costs of injury and loss of life from disasters, statistics for 2011 alone indicate economic damages from natural disasters in the United States exceeded $55 billion, with 14 events costing more than a billion dollars in damages each. One way to reduce the impacts of disasters on the nation and its communities is to invest in enhancing resilience—the ability to prepare and plan for, absorb, recover from and more successfully adapt to adverse events. Disaster Resilience: A National Imperative addresses the broad issue of increasing the nation's resilience to disasters. This book defines "national resilience", describes the state of knowledge about resilience to hazards and disasters, and frames the main issues related to increasing resilience in the United States. It also provide goals, baseline conditions, or performance metrics for national resilience and outlines additional information, data, gaps, and/or obstacles that need to be addressed to increase the nation's resilience to disasters. Additionally, the book's authoring committee makes recommendations about the necessary approaches to elevate national resilience to disasters in the United States. Enhanced resilience allows better anticipation of disasters and better planning to reduce disaster losses-rather than waiting for an event to occur and paying for it afterward. Disaster Resilience confronts the topic of how to increase the nation's resilience to disasters through a vision of the characteristics of a resilient nation in the year 2030. Increasing disaster resilience is an imperative that requires the collective will of the nation and its communities. Although disasters will continue to occur, actions that move the nation from reactive approaches to disasters to a proactive stance where communities actively engage in enhancing resilience will reduce many of the broad societal and economic burdens that disasters can cause.
Keywords: Earth Sciences; Policy for Science and Technology; Conflict and Security Issues

Facilitating Climate Change Responses: A Report of Two Workshops on Knowledge from the Social and Behavioral Sciences - National Research Council (The National Academies Press, 2010)
The William and Flora Hewlett Foundation, understanding the need for policy makers at the national level to entrain the behavioral and social sciences in addressing the challenges of global climate change, called on the National Research Council to organize two workshops to showcase some of the decision-relevant contributions that these sciences have already made and can advance with future efforts. The workshops focused on two broad areas: (1) mitigation (behavioral elements of a strategy to reduce the net future human influence on climate) and (2) adaptation (behavioral and social determinants of societal capacity to minimize the damage from climate changes that are not avoided). Facilitating Climate Change Responses documents the information presented in the workshop presentations and discussions. This material illustrates some of the ways the behavioral and social sciences can contribute to the new era of climate research.
Keywords: Environment and Environmental Studies; Earth Sciences